The Influence of the Project Based Learning (PJBL) Learning Model on Student Learning Outcomes in History Subjects - Dewi, Ratna; Chairunisa, Eva Dina; Suriadi, Aan; Syafarudin, Nur (UNIVERSITAS MUHAMMADIYAH METRO, 2025)
The aim of this research is to determine the effect of the Project Based Learning learning model on student learning outcomes in history subjects. This research uses quantitative methods. The sample was selected using random sampling. Data analysis techniques use normality test, homogeneity test, t-test, u-test. This can be proven by obtaining an average post-test score between experimental class students and control class students. 0.000 and the significance level value = 0.05, so 0.000 < 0.05 so that Ho is rejected and Ha is accepted. Based on these calculations, it can be concluded that the experimental class learning was higher than the control class. The impact of this research is that after carrying out project-based learning students can improve learning outcomes because from the learning process students are directly involved in the learning process whereas before this research was carried out students were still using conventional learning methods so student learning outcomes were low. The conclusion of this research is that there is an influence of the Project Based Learning learning model on student learning outcomes in history subjects.